2017
DOI: 10.35808/ersj/659
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Crude Oil Price in Biodiesel and its Implication on the Production of Palm Oil: The Case of Indonesia

Abstract: Over the last five years (2012-2016) there has been a rise in world oil prices which were very noticeable on an average of 17,85 percent per year. This increase encouraged the increased use of alternative fuels, one of which was biodiesel. It was estimated that the average increase in global biodiesel production amounted to 43.18 percent per year. Because one of biodiesel feedstocks was CPO, the increased production of biodiesel causes CPO export demand to increase simultanesly. The Bio-diesel utilization is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 7 publications
1
10
0
1
Order By: Relevance
“…work and technology. Thus, there is a relationship between production and input in the form of maximum output produced by certain inputs or what is called the production function (Murti, 2017).…”
Section: Theoretical Basismentioning
confidence: 99%
See 1 more Smart Citation
“…work and technology. Thus, there is a relationship between production and input in the form of maximum output produced by certain inputs or what is called the production function (Murti, 2017).…”
Section: Theoretical Basismentioning
confidence: 99%
“…Agricultural development in Indonesia is considered important from the overall national development. Murti (2017) states that demand for plantation products drives economic growth, as well as Sophia, Gnych, Dermawan, Komarudin, and Okarda (2017) stated that the demand for plantation products encourages investment and is influenced by macro and institutional policies.…”
mentioning
confidence: 99%
“…Murti (2017) studied the influence of crude oil price in biodiesel and its implication on the production of palm oil in Indonesia. Murti emphasized that the higher prices of crude oil increase the competitiveness of biodiesel as an alternative to fossil diesel and subsequently lift demand for palm oil (Murti, 2017). Prochazka and Honig (2018), in their economic analysis of replacing dieselfuel by crude palm oil in Indonesian power plants on the back of international diesel price evolution, showed that the move may be profitable given the increasing prices of diesel and the weakening Indonesian currency against the US dollar (Prochazka & Honig, 2018).…”
Section: Global Fuel Prices Affecting the Biodiesel Economicsmentioning
confidence: 99%
“…However, as many countries utilize palm oil in their biodiesel, export demand from Indonesia would increase capping the availability of palm oil for domestic consumption. The higher palm oil demand then increases the prices of biodiesel (Murti, 2017).Despite this likely downside the Indonesian government is planning to raise the blend fron 20% to 30%(The Jakarta Post, 2018). Similarly, the Malaysian government mandated an increase in biodiesel blend rate from 7% to 10% on the back of falling prices of palm oil and record-high inventories in the region (Kana, 2019).The decision was apparently based on a previous study (Applanaidu, et al, 2014) that saw little increase in the palm oil domestic price (0.07%) due to higher blend of 10%.…”
Section: Implications Of Higher Biodiesel Blend In the Regionmentioning
confidence: 99%
“…The aim of this study is to examine the impact of CPO price fluctuations on corporate default risk (CDR) using firm-level data for Indonesia. This study fills an important gap in the literature because the impact of CPO price fluctuations in Indonesia is widely discussed in the macro level (Murti, 2017;Wihardja, 2016;Aziz and Applanaidu, 2017;and Winardi et al, 2017) but rarely explored at the firm level. Several studies discuss the impact of financial management on the performance of palm oil firms but have not specifically addressed how CPO impacts CDR.…”
Section: Introductionmentioning
confidence: 99%